SAT0672 Is ultrasound remission achievable in patients with early rheumatoid arthritis?. (12th June 2018) - Serban, T.; Azzolin, I.; Satulu, I.; Mihai, C.M.; Massazza, G.; Bojinca, M.; Iagnocco, A.
Abstract : Background: In rheumatoid arthritis (RA) the "window of opportunity" has a crucial role for better long-term outcomes. 1 The ACR/EULAR remission criteria for RA are mostly represented by clinical parameters, while ultrasound (US) is not included. 2 However, in early diagnosed and early treated patients, who fulfil the remission criteria, residual US modifications can be identified. 3 Objectives: The aim of this study was to investigate whether significant US-detectable differences between early RA (ERA) patients treated for one year and healthy controls (HC) are present. Methods: We enrolled in this cross-sectional study consecutive patients with ERA at 1 year after having initiated RA disease-modifying (DMARD) therapy and who had received treatment following RA recommendations. Only patients who had fulfilled EULAR/ACR 2010 criteria for RA 4 and with symptoms duration of less than 1 year at treatment initiation were included. US exams were performed in 10 joints bilaterally (wrist, MCP II-V) by using both gray-scale and Doppler for evaluating synovitis was graded according to a semi-quantitative 4-point scale (0–3). A total US score for synovitis was calculated by adding the values recorded at each joint site. The presence of erosions was also recorded. Finally, US results obtained in patients were compared to those detected in HC. Results: 84 subjects were enrolled – 45 ERA patients and 39 HC. In ERA patients the mean duration of symptoms prior to diagnosis was 3.5±3.5 months. The demographic, clinical and US data are reported in table 1. Conclusions: Patients with RA, who had been early diagnosed and early treated, after 1 year of tight control had still US inflammatory and erosive changes compared to HC. US assessment gives an added value to clinical evaluation in ERA, for its capacity to detect residual inflammatory abnormalities, even under optimised treatment and consequent structural lesions. References: [1] van Nies JAB, et al. Ann Rheum Dis2015;74:806–812. [2] Bykerk VP1, Massarotti EM. Rheumatology2012;51(Suppl 6):vi16–20. [3] Vergara F, et al. Reumatol Clin2017Mar 18. [4] Aletaha D, et al. Arhritis Rheum2010;62:2569–2581. Disclosure of Interest: None declared